FLAVOR FORMATION IN FRUIT AND VEGETABLES - Kustyawati, Maria Erna (Jurnal Teknologi & Industri Hasil Pertanian, 2008)
Flavor is an important sensory aspect of the overall acceptability of food. The sensation of flavor is comprised of aroma, taste, which are most affecting the sensation of flavor, texture and psychological perception. Determination of flavor is most emphasized on the constituents flavor rather than the mechanism and metabolic pathway. However, this paper will have a discussion on the flavor formation in fruit and vegetables. Key words: Flavor, flavor chemistry, flavor formation, aroma, taste.